The Influence of Monsoon Winds on Humidity, Cloud Cover, and Rainfall in Bengkulu City - Warahma, Ella; Lizalidiawati, Lizalidiawati; Herawati, Tuti; Irkhos, Irkhos (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
The city of Bengkulu, which borders the Indian Ocean, has unique weather and climate. The ENSO phenomenon in 2023 will also strengthen the impact of monsoon winds on weather parameters in Bengkulu City. This research aims to analyze the influence of monsoon winds on air humidity, cloud cover and rainfall in Bengkulu City during 2022-2024. Data including wind speed and direction, humidity, cloud cover, and rainfall, were analyzed using WRPLOT View, ArcGIS, Panoply, and Excel software. The method used is descriptive, quantitative and statistical analysis. The results show that during the Northwest Monsoon (January 2022–2024), the dominant winds are from the northwest and northeast with cloud cover (80%) and the highest rainfall is 449 mm/month and the lowest is 208 mm/month. In Transition Monsoon I (April 2022–2024), the wind direction is from the northwest, the highest humidity is 94%, cloud cover (75%) and rainfall is medium to high. In the Southeast Season (August 2022), the wind direction varies greatly with the highest (95%) and lowest (77%) air humidity and the highest rainfall of 558 mm/month. Meanwhile, August and October 2023 will see a decrease in rainfall, where the rainfall will be 10 – 84 mm/month due to the El Niño phenomenon. Transition Season II (October 2022 and 2024) the wind direction varies greatly, namely from the southeast, northwest and north, rainfall varies from low to high. The highest correlation coefficient for rainfall with humidity was 0.45 at the Bengkulu Climatology Station and the lowest was 0.22 at the Bengkulu University Station. The highest correlation with cloud cover was 0.67 at Tanjung Agung Station and the lowest was 0.53 at Bengkulu Climatology Station. This study reveals that the northwest monsoon contributes to high humidity and rainfall, and El Niño will reduce rainfall significantly in 2023. These results indicate that monitoring seasonal winds is very important for predicting hydrometeorological disasters in Bengkulu City.